2020
DOI: 10.1101/2020.03.26.010173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ppd-H1integrates drought stress signals to control spike development and flowering time in barley

Abstract: Highlight 19 We show that Ppd-H1 integrates photoperiod and drought stress signals via 20 FLOWERING LOCUS T 1 (FT1) and the downstream MADS-box genes BM3 and BM8 21 to modulate reproductive development, and shoot and spike morphology in barley. 22Abstract 23 Drought impairs growth and spike development and is therefore a major cause of yield 24 losses in the temperate cereals barley and wheat. Here, we show that the photoperiod 25 response gene PHOTOPERIOD-H1 (Ppd-H1) interacts with drought stress signals t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…This could explain the faster transition to the reproductive stage that occurred in Rum compared to Steptoe under LD and SD conditions and particularly in response to drought stress under SD conditions. Such differences in Vrn-H1 gene expression between genotypes were reported previously where higher expression levels were detected in S42-IL107 compared with Scarlett under LD conditions irrespective of drought treatment [21]. In this study, both tested genotypes carried different Vrn-H1 alleles where Rum has an insertion (Vrn-H1-7) and Steptoe has a deletion (Vrn-H1-4) at Vrn-H1 rst intron [22], which might explain the differential gene expression in response to different treatments.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This could explain the faster transition to the reproductive stage that occurred in Rum compared to Steptoe under LD and SD conditions and particularly in response to drought stress under SD conditions. Such differences in Vrn-H1 gene expression between genotypes were reported previously where higher expression levels were detected in S42-IL107 compared with Scarlett under LD conditions irrespective of drought treatment [21]. In this study, both tested genotypes carried different Vrn-H1 alleles where Rum has an insertion (Vrn-H1-7) and Steptoe has a deletion (Vrn-H1-4) at Vrn-H1 rst intron [22], which might explain the differential gene expression in response to different treatments.…”
Section: Discussionsupporting
confidence: 83%
“…A similar trend was reported by [51] where the developmental stage of the apical meristem was similar in introgression lines carrying Ppd-H1 under control and stress conditions. In a recent study, [21] found that the expression of Ppd-H1 was not affected in response to drought under LD conditions in two tested genotypes. Still, the same study concluded that Ppd-H1 integrates photoperiod and drought stress signals to ne-tune reproductive development in barley.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…and HvBM8, barley homologues of Arabidopsis APETALA1/FRUITFUL (AP1/FUL), which were correlated with the development of inflorescence (Digel et al, 2015;Ejaz and von Korff, 2017;Gol et al, 2021). In contrast to Bowman, BW290, and HIF 10_190, we observed overall low VRN-H1 transcript abundance in HIF 10_003.…”
Section: Gene Expression Analysis Reveals That Phenotypic Differences...mentioning
confidence: 58%
“…Barley (Hordeum vulgare) photoperiod response gene PHOTOPERIOD-H1 (Ppd-H1) is a homolog to Arabidopsis PRR. Gol et al found that mild drought causes a decrease in the number of spikelet and a delay in floral development in spring barley cultivars with a natural mutation in ppd-H1, but has little effect on the introgression lines carrying wild-type Ppd-H1 (Gol et al, 2021). This result suggests the critical role of circadian component PRRs in potential drought adaptations.…”
Section: Circadian Clock Gates Aba Signaling In Response To Drought S...mentioning
confidence: 99%